An Unusual Presentation of a Carcinoid Tumor of the Common Bile Duct - Jethava, Ashif; Muralidharan, Visvanathan; Mesologites, Thalia; Stoica-Mustafa, Elena; Dasanu, Constantin A (JOP. Journal of the Pancreas, 2013)
Context Carcinoid tumors arising from the bile ducts account for only a small fraction of biliary tract cancers. Case report We report herein a 42-year-old man with a carcinoid tumor of the common bile duct. He presented with abdominal pain, bloating and dyspepsia. Clinicolaboratory and imaging studies suggested a probable obstructive common bile duct lesion. The patient underwent an endoscopic retrograde cholangiopancreatography with a stent placement in view of common bile duct decompression. Persistence of symptoms prompted a laparotomy and pancreaticoduodenectomy that revealed a well-differentiated carcinoid tumor originating in the common bile duct. Conclusion Clinician’s familiarity with the unusual sites of origin of neuroendocrine tumors and/or atypical presentation of such tumors may facilitate their early recognition and allow for a timely intervention. Image: Nodular mass in the common bile duct lumen.